2020
DOI: 10.1093/noajnl/vdaa048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of circulating miR-371a-3p for the management of patients with intracranial malignant germ cell tumors

Abstract: Background The current biomarkers alpha-fetoprotein (AFP) and human chorionic gonadotropin (HCG) have limited sensitivity/specificity for diagnosing malignant germ cell tumors (GCTs) and “marker-negative” patients require histological confirmation for diagnosis. However, GCTs at intracranial sites are surgically relatively inaccessible and biopsy carries risks. MicroRNAs from the miR-371~373 and miR-302/367 clusters are over-expressed in all malignant GCTs and, in particular, miR-371a-3p show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…Other have demonstrated that these microRNAs could be detected in other bodily fluids apart from blood derivatives (malignant pleural effusions, seminal plasma, hydrocele fluid, cerebral spinal fluid), which gave further information about these biomarkers [ 67 , 83 , 98 ]. The evidence of stability in other fluids argues in favor of their use, for instance, in a metastatic context and in extragonadal GCTs, which was further confirmed [ 99 , 100 ]. These microRNAs were not detected in urine and studies in seminal plasma disclosed issues hampering the use of this bodily fluid for the diagnosis of TGCTs because of higher levels in the healthy control population compared to those observed in serum [ 83 , 101 , 102 , 103 ].…”
Section: Micrornasmentioning
confidence: 83%
“…Other have demonstrated that these microRNAs could be detected in other bodily fluids apart from blood derivatives (malignant pleural effusions, seminal plasma, hydrocele fluid, cerebral spinal fluid), which gave further information about these biomarkers [ 67 , 83 , 98 ]. The evidence of stability in other fluids argues in favor of their use, for instance, in a metastatic context and in extragonadal GCTs, which was further confirmed [ 99 , 100 ]. These microRNAs were not detected in urine and studies in seminal plasma disclosed issues hampering the use of this bodily fluid for the diagnosis of TGCTs because of higher levels in the healthy control population compared to those observed in serum [ 83 , 101 , 102 , 103 ].…”
Section: Micrornasmentioning
confidence: 83%
“…GCT are associated with up-regulation of the miR-371~373 and miR-302 clusters, disregarding tumour site, age, or histopathologic type [ 96 ]. MiR-371a-3p was identified as a reliable marker in the differential diagnosis between germinoma and Langerhans cell histiocytosis, granting an early detection in cases where imaging studies and serum/CSF work-up are inconclusive [ 97 ]. A prospective observational cohort study is currently recruiting patients to evaluate whether miRNA 371 can be used as a prognostic marker for the risk of GCT recurrence [ 98 ].…”
Section: Genetic Approachmentioning
confidence: 99%
“…Carboplatin monotherapy, at modest dosing, has also been successfully utilized in intracranial germinoma to allow a reduction in subsequent radiotherapy doses 19 . Furthermore, we recently reported successful vinblastine monotherapy induction, prior to radiotherapy, in a patient with intracranial germinoma 20 . The patient presented with complete loss of vision, and imaging demonstrated a suprasellar lesion, measuring 36 × 28 × 23 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Vision returned within 4 days of starting vinblastine and after further review, the diagnosis was revised to germinoma. After dramatic radiological reduction in tumor size after just two vinblastine doses (to 21 × 19 × 12 mm; a 77% volume reduction), a 12‐week induction course was delivered, with excellent response, prior to radiotherapy 20 . Importantly, both carboplatin and vinblastine schedules can be successfully delivered peripherally without recourse to placement of a central venous access device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation